2018
DOI: 10.1590/1678-98652018000200009
|View full text |Cite
|
Sign up to set email alerts
|

The under-reporting of energy intake influences the dietary pattern reported by obese women in the waiting list for bariatric surgery

Abstract: Objective To verify the interference of the energy intake under-reporting in the determination of the dietary patterns and nutrient intakes reported by obese women in the waiting list for bariatric surgery. Methods The study included 412 women aged 20 to 45 years with a body mass index ranging from 35 to 60kg/m2 who were on waiting list for bariatric surgery. Data from three reported food intake and physical activity, body weight, and height were used for estimating the reported energy intake, physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We speculate that a cluster analysis using multiple quantitative and possibly semi-quantitative biomarkers will provide vital insight into the foods that are misreported. The value of identifying what foods were being underreported as well as the difficulty of doing so without using biomarkers is illustrated by a Brazilian study performed in obese women prior to bariatric surgery (30). The study found that the under-reporters reported lower intakes of foods with high energy density but with similar intakes of calories provided by healthy foods (fruits, leafy vegetables, and vegetables) compared to those of plausible reporters.…”
Section: Dietary Misreportingmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that a cluster analysis using multiple quantitative and possibly semi-quantitative biomarkers will provide vital insight into the foods that are misreported. The value of identifying what foods were being underreported as well as the difficulty of doing so without using biomarkers is illustrated by a Brazilian study performed in obese women prior to bariatric surgery (30). The study found that the under-reporters reported lower intakes of foods with high energy density but with similar intakes of calories provided by healthy foods (fruits, leafy vegetables, and vegetables) compared to those of plausible reporters.…”
Section: Dietary Misreportingmentioning
confidence: 99%
“…The study found that the under-reporters reported lower intakes of foods with high energy density but with similar intakes of calories provided by healthy foods (fruits, leafy vegetables, and vegetables) compared to those of plausible reporters. This reporting behavior influenced the determination of dietary patterns by exploratory factor analysis, in which the principal component analysis with VARIMAX rotation was applied for the selection of food groups that composed the matrix and then used for dietary pattern interpretation (30). By combining diet factor analysis with biomarker data on energy, protein, sugar, sodium, and potassium, it should be possible to infer if these differences were due to actual dietary intake differences.…”
Section: Dietary Misreportingmentioning
confidence: 99%
“…A multicultural survey of Latin Americans revealed that socio‐demographic characteristics, physical activity level and nutritional status are potentially associated with mis‐reporting of EI, where the highest frequency of under‐reporting was in women, older population groups, groups with less education and populations with overweight, while over‐reporting was higher in younger groups with low socio‐economic status, underweight or normal weight (Previdelli et al, 2019). Studies with Brazilian populations also assessed the presence of mis‐reporting in the assessment of EI, with under‐reporting being more prevalent than over‐reporting (Lopes et al, 2016; Nascimento et al, 2020; Pfrimer et al, 2014; Ravelli et al, 2018; Scagliusi et al, 2008). Furthermore, the frequency of under‐reporting was higher in populations with comorbidities and in older populations (Lopes et al, 2016; Nascimento et al, 2020; Pfrimer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%